2016
DOI: 10.1021/acsami.6b07528
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Au-Coated Magnetic Nanoparticles and Their Application in Bacteria Detection via a SERS Method

Abstract: This study proposes a facile method for synthesis of Au-coated magnetic nanoparticles (AuMNPs) core/shell nanocomposites with nanoscale rough surfaces. MnFe2O4 nanoparticles (NPs) were first modified with a uniform polyethylenimine layer (2 nm) through self-assembly under sonication. The negatively charged Au seeds were then adsorbed on the surface of the MnFe2O4 NPs through electrostatic interaction for Au shell formation. Our newly developed sonochemically assisted hydroxylamine seeding growth method was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
104
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 208 publications
(110 citation statements)
references
References 64 publications
2
104
0
Order By: Relevance
“…Poudyal et al [107] reported a novel method for preparing a FePtAu core-shell structure using solution phase chemistry combined with solvothermal annealing, which showed great promise for various optical, sensing, and biomedical applications. Wang et al [108] designed Au-coated MnFe2O4 nanoparticles, which were first modified with a uniform PEI layer (2 nm). The negatively charged Au seeds were then adsorbed onto the surface of the MnFe2O4 nanoparticles via electrostatic interaction during the formation of the Au shell.…”
Section: Gold-coated Mnpsmentioning
confidence: 99%
“…Poudyal et al [107] reported a novel method for preparing a FePtAu core-shell structure using solution phase chemistry combined with solvothermal annealing, which showed great promise for various optical, sensing, and biomedical applications. Wang et al [108] designed Au-coated MnFe2O4 nanoparticles, which were first modified with a uniform PEI layer (2 nm). The negatively charged Au seeds were then adsorbed onto the surface of the MnFe2O4 nanoparticles via electrostatic interaction during the formation of the Au shell.…”
Section: Gold-coated Mnpsmentioning
confidence: 99%
“…Gold-coated magnetic nanoparticles were synthesized employing hydroxylamine seeding based on a sonochemical method [62]. The nanoparticles had the same size and shape, were stable, and possessed excellent magnetic responsivity and strong surface-enhanced Raman spectroscopy (SERS) activity.…”
Section: Introductionmentioning
confidence: 99%
“…The upgrade of such sorbents for simultaneous use in water purification and contaminant detection is a challenging task but of great practical interest for sensing applications, thus following current interest in developing multifunctional nanomaterials. In this context, the development of SERS-active magnetic nanomaterials has attracted much attention, because it provides innovative platforms that combine magnetic responsiveness and the ability for Raman monitoring within a single material [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Penicillin G (PG) belongs to the β-lactam antibiotics family whose structure is composed of a five-membered sulfur-containing thiazolidine ring fused to a beta-lactam ring and a phenyl ring attached to the side chain ( Figure S1, Supporting Information).…”
Section: Introductionmentioning
confidence: 99%